(untitled) (Semiárida, 2023)
The purpose of the experience was to characterize the porous system in different land uses and determine whether the physical-water indicators under the mixed rotation approach (annual crops-pastures) approach the levels of the indicators under the use with permanent pasture of grass (baseline) for loam soils of the Semiarid Pampas Region. On petrocalcic Paleustoles, 3 different uses were selected, corresponding to long-term trials, permanent pasture of Weeping Grass (LL) considered as baseline soil, perennial pastures of Festuca+Agropiro (F+A) and Alfalfa+Agropiro (A+ A) and agricultural use (Ag). Regarding these uses, indicators were determined such as organic matter (total, young and old), apparent density, maximum apparent density, relative compaction, critical humidity, total porosity, macroporosity, resistance to penetration, infiltration and roots. The values of the indicators evaluated in the two perennial pastures (F+A and A+A), were found closer to the LL values than to the Ag use, although particularly the A+A pasture was the one that was closest to the reference situation. Soil use had a greater impact in the first 6 cm of depth in most indicators, although the results demonstrate the important contribution under A+A use in total porosity, macropores, apparent density and roots at greater depth. These results demonstrate the potential of perennial pastures, and even more so if they include legume species, in the recovery of physical and biological fertility in soils that are in the process of degradation. Director: Fernández, Romina Co-director: Quiroga, Alberto Raúl